Analisis Metode Pembelajaran Sejarah Kebudayaan Islam Di MTs Darul Huda Marelan - Amalia, Chairani (Educate: Jurnal Ilmu Pendidikan dan Pengajaran, 2023)
This study aims to describe the Islamic Cultural History (SKI) learning method at MTs Darul Huda Marelan. The focus of this research is to: discuss the methods used by Islamic Cultural History teachers at MTs Darul Huda Marelan, whether the learning methods used are appropriate when the learning process takes place. This research uses a qualitative approach with a descriptive type. The collection of data used in this study is in the form of observation, interviews and documentation. In seeking the validity of the data, researchers triangulate sources, observations and method triangulation, and researchers also extend attendance. The subjects used were the Darul Huda Marelan Madrasah Principal, deputy Madrasah Principal, Islamic Cultural History Teacher, and class IX students. Based on the results of observations made by researchers at MTs Darul Huda Marelan school with one of the Islamic Cultural History (SKI) subject teachers, information was obtained that the learning methods used in learning were lecture, question and answer, and discussion methods. So that in such a learning method it still seems monotonous and boring for students. The solution given by the Islamic Cultural History teacher is that usually the cultural history teacher, before starting class learning, has first prepared the materials to be studied by photocopying or printing the material to be studied.